Matrix revolutions - Silver, Joel.; Wachowski, Lana, 1965-; Wachowski, Lilly, 1967-; Alice, Mary, 1941-; Bellucci, Monica, 1968-; Bliss, Ian.; Davis, Essie; Fishburne, Laurence, III, 1961-; Moss, Carrie-Anne, 1970-; Perrineau, Harold; Smith, Jada Pinkett, 1971-; Reeves, Keanu; et al. (Burbank, CA : Warner Home Video, 2004)
Neo remains unconscious in the real world, caught in a mysterious subway station that lies between the machine world and the matrix. Bane is still a conduit for Agent Smith, who continues to grow more out of control. Meanwhile, the sentinels are coming dangerously close to Zion. Trinity and Morpheus bargain with The Merovingian to free Neo. Neo, after meeting The Oracle, decides he must leave Zion and go for the machine mainframe. One final battle must ensue, and the future of both races is at stake.
Matrix reloaded
Director of photography, Bill Pope ; editor, Zach Staenberg ; original music, Don Davis ; costume designer, Kym Barrett ; production designer, Owen Paterson ; visual effects supervisors, John Clinton [and others] ; special effects supervisor, Steve Courtley.
Mary Alice, Monica Bellucci, Ian Bliss, Essie Davis, Laurence Fishburne, Carrie-Anne Moss, Harold Perrineau, Jada Pinkett smith, Keanu Reeves, Hugo Weaving, Lambert Wilson.
MPAA rating: R; for sci-fi violence and brief sexual content.
DVD, widescreen (2.40:1) presentation; 5.1 Dolby Digital surround.
English or German, English, German, Swedish, Norwegian, Danish, Finnish, Icelandic subtitles; Hearing impaired: English, German.
110053
Keywords: Computer systems -- Drama; Computers -- Drama; DVD-Video discs; Drama; Dystopian films; Feature films; Fiction films; Science fiction films; Video recordings for the hearing impaired